MURCIÉLAGOS EN BOSQUES ALTO-ANDINOS, FRAGMENTADOS Y CONTINUOS, EN EL SECTOR OCCIDENTAL DE LA SABANA DE BOGOTÁ (COLOMBIA) - Pérez Torres, Jairo; Laboratorio de Ecología de Poblaciones y Comunidades. Unidad de Ecología y Sistemática (UNESIS), Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2004)
The structure and composition of bat communities of the high Andean forest was studied from May, 1998 to April, 1999. The bat species composition and diversity in two isolated fragments surrounded by pastureland was compared with that of two continuous forests. Diversity and abundance of species decreased in fragments, with only a few species dominating (e.g. Artibeus sp., Anoura geoffroyi and Myotis oxyotus). Only frugivore bat species showed a reduction (42%) in species richness in the fragments(Carollia brevicauda, Artibeus hartii, Sturnira bidens, Sturnira ludovici and Sturnira oporaphilum). This result suggests that frugivorous bats may be more prone to extinction due to habitat fragmentation.